Applied Data Science for Exploring Human Resource Management Affecting the Competitiveness of Commercial Banks in Vietnam - Hien, Lam Thanh; Tam, Phan Thanh (Journal of Applied Data Sciences, 2025)
Human resource management is crucial in banking operations and is fundamental for maintaining sustainable development and enhancing the competitiveness of commercial banks. The current challenges in human resource management within banking operations provide notable limits that adversely impact competitiveness. This study seeks to identify the elements impacting human resource management in commercial banks in Vietnam and assess their degree of impact. Considering these issues and their influence on human resource management, the authors suggested strategies to enhance human resource management and bolster the competitiveness of banks. This research employs a blend of qualitative and quantitative methodologies. The study included qualitative approaches, utilizing expert techniques and in-depth interviews with 10 bank directors, supplemented by primary data gathered via 350 questionnaires distributed to staff across 10 commercial banks in 10 regions in Vietnam. SPSS 20.0 and Amos software were utilized to measure the extent of influence of the components. The research found six factors: leadership support, training and development of human resources, workplace environment, employee perks and policies, incentive strategies, monitoring, and assessment. The study finds that control and evaluation have the strongest impact on human resource management. Ultimately, the tool assists banks in maintaining adequate human resource management and enhancing competitive positioning. The novelty of this study showed that human resource management affects the competitiveness of commercial banks with a significance of 0.05. Finally, commercial banks should improve digital human resource development software to provide comprehensive management solutions such as AI-driven recruitment platforms, automated performance evaluations, and human resource analytics tools to enhance efficiency, reducing costs and time to perform tasks. Especially helping bank leaders quickly make the right decisions about human resources. Furthermore, human resources management also contributes to the crystallization of corporate cultural values, building and preserving the bank's brand and identity, and is the driving force and goal for the bank's sustainable development.